Can Micronized Sulfur in Urea Reduce Ammoniacal Nitrogen Volatilization and Improve Maize Grain Yield? - Crusciol, Carlos Alexandre Costa [UNESP]; Almeida, Danilo Silva [UNESP]; Alves, Cleiton José [UNESP]; Soratto, Rogério Peres [UNESP]; Krebsky, Evelin Oliveira [UNESP]; Spolidorio, Eduardo Scarpari [UNESP] (Springer Nature, 2019)
Micronized sulfur (S) in urea may reduce nitrogen (N) loss by ammoniacal N (NH3–N) volatilization and provide a better use for S from oil refineries, thereby improving plant nutrition by providing N and S. The objective of this study was to evaluate the use of urea micronized with S (urea+S) to mitigate NH3–N volatilization and the efficiency of the urea+S as source of N and S for maize (Zea mays L.). Three field experiments were implemented, with maize grown in coarse-, medium-, and fine-textured soils and the following treatments: urea, ammonium nitrate, ammonium sulfate, urea+S enhanced with 13% elemental S (urea+SA), urea+S with 4% elemental S and 9% S in sulfate form (urea+SB), and a control without N application. The leaf N concentrations increased similarly for all the N sources. The leaf S concentrations were greater when the ammonium sulfate and urea+S were applied. The use of micronized S does not decrease the NH3–N volatilization from urea side-dress applied to maize. However, in comparison with ammonium sulfate, the urea+S are a viable alternative for supplying N and S to maize because of their greater operational efficiencies and due to their high N concentrations.
Keywords: Alternative sulfur source; Ammonia; Nitrogen sources; No-till